Greenhouse monitoring system - Ab Wahab, Muhammad Nazrin (2016)
A greenhouse (also called a glasshouse or a hothouse) is a building or complex in which plants are grown. The idea of growing plants in controlled environment can be traced back to the ancient Roman times. At that time, the Roman emperor Tiberius ate a cucumber-like vegetable daily. Method that have been used by the Roman gardeners are similar to that greenhouse system so that the emperor can had that vegetables every day of the year. It is not until the discovery of ‘active’ greenhouses, in which it is possible for the temperature to be increased or decreased manually which appeared at a much later time. Sanga yorok written in the year 1450 in Korea, stated a house which was designed to regulate the temperature and humidity requirements of plants and crops.